The World's emerging stock markets : structure, developments, regulations & opportunities - Park, Keith K. H.; Agtmael, Antoine W. van. (Chicago, Ill. : Probus, 1993)
Of all the astonishing transformations on the global stage to which the last decade has borne witness, perhaps none is so emblematic, or epochal, as the emergence of markets once considered too limited or obscure to merit the attention of serious investors. The World's Emerging Stock Markets, the most current and comprehensive work available on this phenomenon, is an essential addition to every investor's library.
In Korea, Thailand, Mexico, Chile and a host of other nations, stock markets previously shunned as illiquid, or simply too exotic, are evolving at a terrific rate, and drawing in ever more participants. Consider these facts:. The emerging markets' share of world market capitalization will grow from approximately 7 percent to 15-20 percent - a pace more than twice that of the industrialized nations.
Foreign portfolio investment in emerging markets grew from less than $500 million in 1984 to roughly $25 billion in 1991. By the end of the decade, that growth is expected to reach $100 billion. The top 100 stocks among emerging market companies will soon be household names to the world's investors as they launch issues in America, Japan and Europe, appearing with increasing frequency in the global equity markets.
Editors Keith K. H. Park and Antoine W. van Agtmael examine these developing markets both individually and in relation to the global economy. They discuss the opportunities and risks associated with each; describe portfolio management and research techniques designed specifically for these markets; and provide profiles of the stocks issued in each. A series of appendices include fact sheets on emerging market funds and an in dispensable directory of exchanges in emerging stock markets.
The World's Emerging Stock Markets encloses within its covers, literally, a new world's worth of information!
Appendix A: World Market Performance Data in Local Currency Terms -- Appendix B: World Market Performance Data in U.S. Dollar Terms -- Appendix C: IFC Emerging Markets Price Indices in U.S. Dollar Terms -- Appendix D: Closed-End Country Funds Selected Data -- Appendix E: Latin American Country Funds Fact Sheets -- Appendix F: European Country Funds Fact Sheets -- Appendix G: Asian Country Funds Fact Sheets -- Appendix H: Directory of Stock Exchanges in Emerging Markets.
Includes index.
Keywords: Stock exchanges -- Asia; Stock exchanges -- Latin America; Stock exchanges -- Europe; Stock exchanges -- Middle East; Portfolio management